Eggshell conspicuousness is related to paternal brood patch vascularisation in the American thrashers. (1st May 2013) - Hanley, Daniel
Conspicuous blue-green egg colouration has been of interest to scientists and naturalists for more than a hundred years; however, the function of this trait has never been fully understood and has spurred extensive debate. The American thrashers exhibit great variation in egg colouration and patterning, and also show variation in male brood patch development. A recent hypothesis suggests that conspicuous egg colouration has evolved as the product of sexual conflict, where females may create conspicuous eggs to obtain greater amounts of male care, either in the form of male incubation or incubation assistance to prevent their eggs from being vulnerable to visually orienting predators and brood parasites. The American thrashers, a genus comprising of 10 species, exhibits striking variation in egg colouration and patterning, and also show variation in male brood patch development. By using avian visual modelling, I show that blue-green chroma of American thrasher eggs is positively related to their degree of conspicuousness against a nest background, while brown chroma is negatively related. Interestingly, the degree of male brood patch vascularisation is directly related to eggshell conspicuousness in American thrashers. I suggest that in the American thrashers, male brood patch vascularisation has evolved in response to conspicuous eggshell colouration to mitigate visual risks. Here I show that the degree of male brood patch vascularisation is directly related to relative paternal incubation effort in more than 300 North American breeding birds. This suggests that American thrasher species that possess both conspicuous eggs and brood patches, have most likely evolved to keep these conspicuous nest contents concealed, thereby reducing risk of visual detection. I suggest that these patterns are not unique to thrashers, but may extend to several avian families.